Editorial: Globalisation of Economies and Industries - Radosław Rybkowski; Krzysztof Wach (Entrepreneurial Business and Economics Review)
At the beginning of the 21st century we also experience some drawbacks of globalisation. Yes, it “promotes economic and social advancement”, but the progress is not evenly distributes and not “all peoples” enjoy the benefits of globalisation. Growing interdependency has also brought greater competition, this time reaching much further that just neighbouring countries.